Sistema para realização de medidas de luminescência com excitação por raios X - Cebim, Marco Aurelio [UNESP]; Oliveira, Higor Henrique de Souza; Barelli, Nilso [UNESP]; Davolos, Marian Rosaly [UNESP] (FapUNIFESP (SciELO), 2011)
In this work is presented a versatile system for X-ray excited optical luminescence (XEOL) measurements. The apparatus was assembled from a sample holder connected to an optical fiber responsibly for the acquisition of the scintillation signal. The spectrum is registered with a CCD coupled in a spectrograph provided with diffraction gratings. The system performance was analyzed by exciting GdAlO3:Eu3+ 3.0 at.% with X-rays from a diffractometer and measuring the emission spectra. The system can be used to obtain precise and reliable spectroscopic properties of samples with various conformations without the loss of the required safety when dealing with ionizing radiations.
System for x-ray excited optical luminescence (XEOL) measurements
Keywords: Scintillators; Spectroscopy; X-ray phosphors